Pembentukan karakter siswa di sdn 3 bendosari pujon - Atmaranti, Naysalwa Dwi; Syakhira, Martizha Neisya; Annadwi, M Fadlil Afi; Sugiharto, Wildan (Maliki Interdisciplinary Journal, 2025)
This article discusses the character formation of students at SDN 3 Bendosari Pujon. In the era of modern development, many students are already familiar with sophisticated technology, until now students rarely play traditional instruments, with the development of modern tools that may have an impact on the character of students, have an impact on social interactions and the main factors in influencing student character, namely family, teachers, friends, the surrounding environment and learning media. If one of them is not met, the formation of student character will not be formed perfectly. Therefore, the role of all parties, both parents, teachers, and the school environment is very important in creating an educational ecosystem that supports the formation of positive character in students. At SDN 3 Bendosari Pujon, various efforts are made to integrate character values ​​into learning activities, such as through the habituation of discipline, responsibility, cooperation, and respect for others.